Ameliorative Effects of Bovine Lactoferrin on Benzene-Induced Hematotoxicity in Albino Rats - Elazab, Mohamed F. Abou; Elbaiomy, Asmaa E. A.; Ahmed, Mohamed S.; Alsharif, Khalaf F.; Dahran, Naief; Elmahallawy, Ehab Kotb; Mokhbatly, Abdallah A. (Frontiers in Veterinary Science, 2022)
Benzene (Bz) is one of the major products of the petrochemical industry globally, which induces aplastic anemia and leukemia in humans and animals. This study aimed to investigate the modulatory effects of bovine lactoferrin (bLf) on Bz-induced hematotoxicity in albino rats. Eighty male rats were randomly divided into eight groups: corn oil group [2 mL/kg body weight (BW)], bLf groups (100, 200, and 300 mg/kg BW), Bz group (Bz 2 mL/kg BW; corn oil 2 mL/kg BW), and Bz + bLf groups (Bz 2 mL/kg BW; corn oil 2 mL/kg BW; bLf 100, 200, and 300 mg/kg BW). Hematobiochemical results exhibited marked pancytopenia, a significant decrease in total protein, albumin, α2- and γ-globulin, ferritin, serum iron, and total iron-binding capacity (TIBC), and an increase in serum bioactivities of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and erythropoietin hormone levels in Bz-treated rats. Histopathological examination revealed a marked reduction in all hematopoietic cell lines in the bone marrow (BM), necrosis in the white pulp of the spleen and cytosolic hydrops, and apoptosis of hepatocytes in the Bz-treated group. Rats treated with bLf (300 mg/kg BW) revealed marked increases in total protein, albumin, α2- and γ-globulin, ferritin, serum iron, and TIBC levels and decreases both in ALP and LDH bioactivities and erythropoietin hormone levels compared with the Bz-treated group. Histopathological results were concomitant with hematobiochemical parameters in rats treated with bLf (300 mg/kg BW), almost showing restoration of the normal cellularity of BM, the architecture of red and white pulps of the spleen, and even the normal hypertrophy of hepatocytes compared with the control groups. To conclude, bLf (300 mg/kg BW) can be recommended to treat Bz-induced hematotoxicity.